2015
DOI: 10.1111/ejss.12243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of K2SO4 concentration on extractability and isotope signature (δ13C and δ15N) of soil C and N fractions

Abstract: Determination of the labile soil carbon (C) and nitrogen (N) fractions and measurement of their isotopic signatures ( 13 C and 15 N) has been used widely for characterizing soil C and N transformations. However, methodological questions and comparison of results of different authors have not been fully solved. We studied concentrations and 13 C and 15 N of salt-extractable organic carbon (SEOC), inorganic (N-NH 4 + and N-NO 3 − ) and organic nitrogen (SEON) and salt-extractable microbial C (SEMC) and N (SEMN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The model is also confirmed in soils of the substrate age gradient in Hawaii [14]. These outstanding works were followed by a number of new evidences, confirming the 15 N-enrichment of soil microbial biomass [20,22,26,30,32], as well as of some species of microorganisms during their cultivation on different nitrogen-containing media [28,33]. Single studies confirmed the proposed model by a laboratory incubation experiment with the soil [20] and by the analysis of soils of different land-use systems [32].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The model is also confirmed in soils of the substrate age gradient in Hawaii [14]. These outstanding works were followed by a number of new evidences, confirming the 15 N-enrichment of soil microbial biomass [20,22,26,30,32], as well as of some species of microorganisms during their cultivation on different nitrogen-containing media [28,33]. Single studies confirmed the proposed model by a laboratory incubation experiment with the soil [20] and by the analysis of soils of different land-use systems [32].…”
Section: Introductionmentioning
confidence: 54%
“…There is a good agreement of δ 15 N micr in humus horizons with previously published results. There are evidence of the values in the range 6.3-7.2‰ for mountain-meadow alpine soils [22]; and within 4.7-5.9‰ for soils of coniferous and mixed forests in Austria [26], coniferous plantations in Central China [32], and grass ecosystems in Kansas prairies [31]. Higher values (7-11‰) were obtained for plowed Luvisol in France [20] and for soils of the elevation gradient in northern Arizona [14].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Soil microbial carbon was determined by the fumigationextraction method (Vance et al, 1987), which involves the fumigation of one sample with ethanol-free chloroform followed by extraction of the organic carbon from the fumigated and nonfumigated samples with 100 mL of 0.5 M K 2 SO 4 . The organic C content from all samples (non-fumigated and fumigated) was quantified using the continuous flow autoanalyzer (Innovox TOC Analyzer, Sievers), with the results from the non-fumigated sample representing the salt-extractable organic C (Makarov et al, 2015). Microbial biomass C was calculated according to the following formula:…”
Section: Sample Analysesmentioning
confidence: 99%
“…There are many studies on the extractable organic N and dissolved organic N in soils to predict N mineralization, N leaching, and to evaluate agricultural (nutrient) management practices (Curtin et al, 2006;Ros et al, 2009), but very few on determining δ 15 N values of WEN or WEON (Makarov et al, 2015). HWEN (or WEN) could be divided into two parts of organic N and inorganic N (NO 3 --N and NH 4 + -N).…”
Section: Amounts and δ 15 N Values Of Hot Water And Water Extraction mentioning
confidence: 99%